Propagation of radiowaves - Barclay, L. W. (IET electromagnetic waves series ;, 2012)
This edition updates and continues the series of books based on the residential courses on radiowave propagation organised by the IEE/IET. The first course was held in 1974, with lectures by H. Page, P. Matthews, D. Parsons, M.W. Gough, P.A. Watson, E. Hickin, T. Pratt, P. Knight, T.B. Jones, P.A. Bradley, B. Burgess and H. Rishbeth. That was seen as a standalone course, but the need was recognised again and led to a succession of courses held every two or three years starting in 1986. A book Radiowave Propagation, edited by M.P.M. Hall and L.W. Barclay, was published by the IEE in 1989 based on the 1986 course. Following the fifth course in 1994, the lecture notes were published by the IEE in 1996 in Propagation of Radiowaves, edited by M.P.M. Hall, L.W. Barclay and M.T. Hewitt. This was succeeded by a second edition in 2003, edited by Les Barclay, based on the eighth course held in 2000. This third edition is loosely based on the 12th course organised by the IET in 2007, but because of the passage of time since that course it includes more recent updating.